Cigarette smoke extract-induced BEAS-2B cell apoptosis and anti-oxidative Nrf-2 up-regulation are mediated by ROS-stimulated p38 activation. (8th September 2014) - Lin, Xi-Xi; Yang, Xin-Fu; Jiang, Jun-Xia; Zhang, Shui-Juan; Guan, Yan; Liu, Ya-Nan; Sun, Yan-Hong; Xie, Qiang-Min
Abstract: Cigarette smoke contains reactive oxygen (ROS) that can cause oxidative stress. It increases the number of apoptotic and necrotic lung cells and further induces the development of chronic airway disease. In this study, we investigated the effects of cigarette smoke extract (CSE) on apoptosis in human bronchial epithelial cells (BEAS-2B). CSE exposure induced ROS generation and p38 mitogen-activated protein kinase (MAPK) activation that are associated with the activation of apoptosis-regulating signal kinase 1 (ASK-1). N-acetylcysteine (a general antioxidant) attenuated the CSE-induced ASK-1 and p38 MAPK activation and cell apoptosis, suggesting a triggering role of ROS in ASK-1/p38 MAPK activation during apoptotic progression. In contrast, the inhibition and knockdown of p38 attenuated the expression of anti-oxidant master NF-E2-related factor 2 (Nrf-2) and CSE-induced apoptosis, suggesting that p38 MAPK modulates Nrf-2 expression and presumably prevents cell apoptosis. Taken together, the data presented in this manuscript demonstrate that the ROS-dependent ASK-1/p38 signaling cascade regulates CSE-induced BEAS-2B cell apoptosis. In addition, anti-oxidative Nrf-2 is also up-regulated by the ROS/p38 signaling cascade in this progression.